TPA for stroke : the story of a controversial drug - Zivin, Justin A. (Oxford University Press, 2011)
Without warning stroke can paralyze, blind, or kill. Some victims recover, but many do not and may even suffer another disabling or fatal attack. The drug known as tPA can drastically reduce the long-term disability associated with stroke, but despite its near-miraculous capabilities and the growing support of most neurologists, it has been slow to win acceptance as the standard of care in emergency departments nationwide. tPA for Stroke chronicles how this remarkable drug came to be tested in stroke victims, its early years in development by the pharmaceutical giant Genentech, and its eventua.